80 Use of an Electronically-controlled Floor Cooling Pad During Heat Stress on Thermoregulatory and Reproductive Performance in Boars. (7th May 2021) - Shirley, Larissa K; Field, Tyler; Schinckel, Allan P; Johnson, Jay S; Stwalley, Robert; Stewart, Kara R
Abstract: This study was designed to evaluate the effects of electronically-controlled floor cooling pads on thermoregulatory and reproductive parameters in boars during heat stress (HS). Boars (n = 24) were randomly assigned to crates with non-functional pads (CON) or pads that were flushed in either 8-min intervals or when the pad reached 28.5°C (FLUSH). For 3 d, boars were subjected to cyclical HS (28 to 35°C; >65% relative humidity). Boars were fed 2.4 kg/d and daily feed intake was recorded. Respiration rate (RR), rectal temperature (Rtemp) and skin temperature were recorded every 2 h during HS (via IR camera), testicular temperature was recorded twice daily. Semen was collected d7 and d14 before HS, the day following HS and weekly for 6 weeks and evaluated for volume, sperm concentration, motility, progressive motility, morphological abnormalities, and viability. After 2 h of HS, FLUSH boars had reduced RR (P < 0.001) and RTemp (P < 0.001) when compared to control boars, and this difference was maintained throughout HS. Skin and testicular temperature were reduced in FLUSH vs. CON boars after 6 h of HS (P < 0.05). Semen volume was greater in FLUSH vs CON boars (P = 0.01) resulting in a tendency for an increase in total sperm per ejaculate (P = 0.075). From weeks 2 to 5 post-HS, FLUSH boars had increased motility (P = 0.006) and progressive motility (P = 0.001), with corresponding increases in sperm kinematic motion parameters when compared to CON boars. The number of morphologically normal sperm cells were increased (P = 0.006) in FLUSH vs CON boars due to reduced distal droplets (P = 0.033) and proximal droplets (P < 0.001). Abnormal acrosomes were reduced (P < 0.001) in FLUSH vs CON boars at week 3 post-HS. In summary, electronically controlled cooling pads effectively reduced negative thermoregulatory indicators of HS and minimized or removed the negative impacts of HS on semen quality in boars.